The Internalization of Religious Values in Shaping Islamic characters of Students at MAN 4 Bojonegoro - Rozi, Fahru; Maarif, M. Jauharul (Universitas Nahdlatul Ulama Sunan Giri, 2021)
Today's world globalization has competitively moved and changed faster. All fields shifted and challenges, including educational institutions. Educational institutions face a serious challenge to be able to follow as well as become the vanguard of global change. Educational institutions become the most important instrument in addressing human resources and are demanded to be able to provide the quality of human resources that are reliable. Education is not merely transferring knowledge to students, but also transferring the universal moral, religious, and humanistic values. By the universal moral transfer, students are expected to have a character that can appreciate other people's lives as reflected in their behavior and self-actualization. One way to shape the character is to internalize the values ​​within school activities. The research shows that: 1) The condition of the student before the internalization of religious values ​​based on the findings of informants in the field is that students have not reflected the character of the Islamic proven,?? 2) A lot of effort made by MAN 4 Bojonegoro in the internalization of religious values in shaping students' Islamic character. 3) The implication achieved after the range of the programs purposed on internalization of religious values ​​in shaping students' Islamic character is that students can understand and practice the religion and character values.